2004
DOI: 10.1038/emm.2004.9
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II receptor blocker attenuates overexpression of vascular endothelial growth factor in diabetic podocytes

Abstract: Abbreviations: RT-PCR, reverse transcription-polymerase chain reaction; VEGF, vascular endothelial growth factor A bstract VEGF expressed in glomerular podocytes, is known to increase vascular perm eability to m acrom olecules. Angiotensin II can stim ulate the release of VEG F, and the protective effects of angiotensin II antagonist against diabetic glom erular injury suggest that the angiotensin II-induced VEG F is an im portant pathogenetic m echanism in the developm ent of proteinuria during diabetic nephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 21 publications
2
27
1
Order By: Relevance
“…It has been recently demonstrated that VEGF expression is upregulated in the kidney, mainly in the podocytes, of streptozotocin diabetic rat. 7,16,18 The podocytes intervene in the filtration barrier function and it has been suggested that enhanced VEGF in podocytes is mediating the increase in albumin permeability in diabetes. 7,16,36 This growth factor is down-regulated in the podocytes of diabetic rats chronically treated with an Ang II receptor antagonist.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been recently demonstrated that VEGF expression is upregulated in the kidney, mainly in the podocytes, of streptozotocin diabetic rat. 7,16,18 The podocytes intervene in the filtration barrier function and it has been suggested that enhanced VEGF in podocytes is mediating the increase in albumin permeability in diabetes. 7,16,36 This growth factor is down-regulated in the podocytes of diabetic rats chronically treated with an Ang II receptor antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…7,16,18 The podocytes intervene in the filtration barrier function and it has been suggested that enhanced VEGF in podocytes is mediating the increase in albumin permeability in diabetes. 7,16,36 This growth factor is down-regulated in the podocytes of diabetic rats chronically treated with an Ang II receptor antagonist. 7 Moreover, Liu et al demonstrated that the increased expression of VEGF in glomeruli directly causes the glomerular hypertrophy that is associated with proteinuria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations